The Effect of Sales Growth and Profitability on Company Value with Debt Policy as Moderating Variables - Jangasih Situngkir; Aloysius Harry Mukti; M.F Christiningrum (Basic and Applied Accounting Research Journal, 2023)
Financial ratio have several function for strategic decision making. Several ratio such as profitability or sales growth are the most important for capital market signal. This Research aims to examine the effect of sales growth and profitability with debt policy as the moderating variable on the value of the manufacturing industry sub-sector of the consumer goods industry listed on the Indonesia stock exchange in 2018-2020. With a total sample of 165 companies. The research methodology is quantitative with multiple linear regression testing with SPSS V23 data processing tools. Based on the result of model 1 testing, the result showed that sales growth had no effect on firm value, and profitability has a positive effect on firm value. The result of model 2 testing, the resulting research shows that sales growth has a positive effect on firm value, Profitability has a positive effect on firm value, debt policy does not moderate the effect of sales growth on firm value and debt policy does not moderate the effect of profitability on firm value.